Poly(ε-caprolactone) films reinforced with chlorhexidine loaded electrospun polylactide microfibers - Y. Marquez; J. Graupera; L. J. del Valle; P. Turon; L. Franco; J. Puiggali (eXPRESS Polymer Letters)
Poly(ε-caprolactone) (PCL) films reinforced with polylactide (PLA) microfibers were prepared by two methodologies: a) melt pressing of an electrospun PLA mat between two PCL films, and b) melt pressing of a co-electrospun mat composed of PLA microfibers and PCL nanofibers. Electrospinning conditions were selected for each polymer to obtain films loaded with 10, 20 and 30 wt% of PLA. Thermal and mechanical properties varied depending on the preparation method. Thus, PLA crystallinity was higher when films were obtained by the co-electrospinning process, as revealed from DSC and synchrotron X-ray diffraction data since cold crystallization of the highly oriented PLA microfibers was favored in the subsequent heating run when they were in close contact with PCL nanofibers. Samples obtained by co-electrospinning also showed higher mechanical properties (e.g. Young modulus) with increasing PLA load. In this case, fracture surfaces showed significant interactions between fibers and the PCL matrix and decreased fiber pull-out. All fabrics were also loaded with chlorhexidine (CHX) as a hydrophilic bactericide agent. A delayed release was observed when the drug was only loaded into the electrospun PLA microfibers, and diffusion varied with the method of preparation. In all cases, samples had a clear bactericide effect against Gram positive and Gram negative bacteria. Nevertheless, the protective effect was slightly lower when CHX was only loaded in the reinforcing PLA microfibers.